Wpływ Sił Podłużnych i Zmian Temperatury na Wielkość Sił Wewnętrznych i Przemieszczeń w Ustrojach Łukowych Langera - Dzieniszewski, W. (Engineering Transactions, 1964)
The subject of the considerations are structures composed of beams, arches and connecting elements of which the beams carry also the horizontal force of the arcs. Accurate computation of such structures, called Langer structures, requires considerable labour, which can be reduced by introducing a suitable scheme with distributed connecting elements. The influence of the external load and temperature changes on the internal forces and displacements of such a system is analysed in the case of axial deformability of all the component elements. The problem reduces to the solution of a Fredholm integral equation of the second kind for the function determining the deflection of the beam due to the forces in the connecting elements.In the numerical example a few diagrams are made for the influence numbers of integral forces and displacements, which are compared with accurate results (with concentrated connection between the arch and the beam) and the solutions obtained by rejecting axial deformability.From the considerations it follows, among other things, that the influence of axial deformability of elements cannot be rejected and that in the case of a great number of connecting elements the introduction of distributed connection of the beam with the arch leads to results of sufficient accuracy.